2020
DOI: 10.1371/journal.pone.0233114
|View full text |Cite
|
Sign up to set email alerts
|

Left powerless: A qualitative social media content analysis of the Dutch #breakthesilence campaign on negative and traumatic experiences of labour and birth

Abstract: Introduction Disrespect and abuse during labour and birth are increasingly reported all over the world. In 2016, a Dutch client organization initiated an online campaign, #genoeggezwegen (#breakthesilence) which encouraged women to share negative and traumatic maternity care experiences. This study aimed (1) to determine what types of disrespect and abuse were described in #genoeggezwegen and (2) to gain a more detailed understanding of these experiences. Methods A qualitative social media content analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 49 publications
4
44
0
Order By: Relevance
“…This was the case for both comparably mild and more severe experiences of mistreatment. This finding corresponds with van der Pijl et al's findings, who identified a theme by the same name in their inductive analysis, which most often referred to emotional consequences that tormented some women even years later [5]. In the present study, more assertive women reacted to mistreatment with resistance and defended their autonomy during childbirth, while less assertive women or women who seemed to have a more traditional understanding of the patientcaregiver relationship submitted themselves to the HCP.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This was the case for both comparably mild and more severe experiences of mistreatment. This finding corresponds with van der Pijl et al's findings, who identified a theme by the same name in their inductive analysis, which most often referred to emotional consequences that tormented some women even years later [5]. In the present study, more assertive women reacted to mistreatment with resistance and defended their autonomy during childbirth, while less assertive women or women who seemed to have a more traditional understanding of the patientcaregiver relationship submitted themselves to the HCP.…”
Section: Discussionsupporting
confidence: 90%
“…A number of Latin American countries for instance have acknowledged obstetric violence as a form of gender-based violence and have passed laws to combat it, following the combined efforts of activists, governmental and non-governmental organisations and researchers, the first of which was Venezuela in 2007 [1]. However, mistreatment during childbirth continues to be a widespread problem around the world, including in high-income countries: Recent studies in Switzerland, Italy, Spain, the Netherlands and the US for instance have shown that a significant proportion of women report that they are mistreated by healthcare professionals (HCP) during childbirth [2][3][4][5][6]. Women have the right to safe, respectful and dignified obstetric care and any form of mistreatment violates fundamental human rights [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not being informed or not being involved in the decision to perform episiotomy can result in negative and even traumatic experiences. Although the studies of Van der Pijl et al 47 and Hollander et al 48 do not represent the feelings and preferences of all women, other studies confirm that women may feel less satisfied after having had an episiotomy. 49 Besides, studies show that information regarding episiotomies is important to increase understanding and feelings of comfort, 50 and that being involved in decision-making is one of the most important contributors to a positive childbirth experience.…”
Section: Discussionmentioning
confidence: 94%
“… 44 45 Although care providers minimally involve women in the decision-making during the second stage of labour, previous studies reported that women highly value their involvement in decision-making during childbirth. 46 Van der Pijl et al 47 examined 438 quotes of women on negative and traumatic childbirth experiences, expressed in the Dutch #breakthesilence campaign and found that lack of informed consent was one of the most frequently expressed types of mistreatment experienced by women during childbirth. Besides, episiotomy was the most frequently mentioned intervention, where women experienced a lack of communication by the care provider, which led to feelings of disrespect.…”
Section: Discussionmentioning
confidence: 99%